El derecho internacional frente al genoma humano y la bioética - Sabogal Murcia, Leonardo (2023)
The human genome, one of the great discoveries of the 20th century, has had innumerable effects in every aspect of human life. This discovery has triggered different processes of human interaction that have proved to be ethically and biologically complex. Furthermore, even though the human genome is truly a concept of scientific and natural research, its consequences have had an impact that is social, legal, and economic in scope, and that must be analyzed with sufficient care. That is why law, as a system of control, power, and order, has offered various interpretations and assumed different points of view that allow it to regulate according to social values and sociolegal traditions, bounded by national, continental, and global archetypes. Bioeth ics leads discussions on the human genome in the field of international law, and it has become the focal point of different fields, as well as an alternative that favors interdisciplinary justice, intimately associated with human rights.